Systematic Literature Review: PBL Model Assisted by PhET Simulation to Improve Students' Critical Thinking Ability - Qothrunnada, Qothrunnada; Rokhmat, Joni (Science Education Doctoral Study Program, Postgraduate, Mataram University, 2024)
This study was conducted to demonstrate the effectiveness of implementing a problem-based learning model in enhancing students' critical thinking skills at the high school level or its equivalent. The type of research carried out was a systematic literature review, following seven stages: formulating research questions, establishing selection criteria, developing search strategies, selecting studies based on selection criteria, assessing research quality, synthesizing results for the research questions, and reporting findings.Article searches were conducted using Google Scholar, SINTA, and ProQuest, with the assistance of the Publish or Perish application, utilizing keywords such as